2021
DOI: 10.3389/fcvm.2021.773473
|View full text |Cite
|
Sign up to set email alerts
|

Novel Knowledge-Based Transcriptomic Profiling of Lipid Lysophosphatidylinositol-Induced Endothelial Cell Activation

Abstract: To determine whether pro-inflammatory lipid lysophosphatidylinositols (LPIs) upregulate the expressions of membrane proteins for adhesion/signaling and secretory proteins in human aortic endothelial cell (HAEC) activation, we developed an EC biology knowledge-based transcriptomic formula to profile RNA-Seq data panoramically. We made the following primary findings: first, G protein-coupled receptor 55 (GPR55), the LPI receptor, is expressed in the endothelium of both human and mouse aortas, and is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 140 publications
0
19
0
Order By: Relevance
“…We hypothesized that TMAO promotes innate immune trans-differentiation of HAECs. We used a novel knowledge-based transcriptomic profiling approach and Venn diagram analysis of TMAO-upregulated genes with 1249 Ingenuity Pathway Analysis (IPA) designed cytokine/chemokine genes, 4340 canonical secretomic genes, and noncanonical secretomic genes including 964 caspase-1-gasdermin D secretomes and 1223 caspase-4 (humans)/11 (mice) secretomes, and 6560 exosome secretomic genes (71)(72)(73)(74). We found that 11 cytokines/chemokines (Figures 5A), 19 canonical/noncanonical secretomic genes (Figures 5B), and 22 exosome secretomic genes (Figures 5C) were overlapped with the TMAO-upregulated genes (RNA-seq).…”
Section: Tmao Activated and Trans-differentiated Haecs Into Innate Im...mentioning
confidence: 99%
“…We hypothesized that TMAO promotes innate immune trans-differentiation of HAECs. We used a novel knowledge-based transcriptomic profiling approach and Venn diagram analysis of TMAO-upregulated genes with 1249 Ingenuity Pathway Analysis (IPA) designed cytokine/chemokine genes, 4340 canonical secretomic genes, and noncanonical secretomic genes including 964 caspase-1-gasdermin D secretomes and 1223 caspase-4 (humans)/11 (mice) secretomes, and 6560 exosome secretomic genes (71)(72)(73)(74). We found that 11 cytokines/chemokines (Figures 5A), 19 canonical/noncanonical secretomic genes (Figures 5B), and 22 exosome secretomic genes (Figures 5C) were overlapped with the TMAO-upregulated genes (RNA-seq).…”
Section: Tmao Activated and Trans-differentiated Haecs Into Innate Im...mentioning
confidence: 99%
“…These bioactive lysophospholipids act primarily by binding to dedicated cell surface receptors in the G protein-coupled receptor family to elicit cellular signaling responses (80,87,88). Although a plethora of research has been conducted with lysophosphatidic acid and sphingosine-1-phosphate, there is emerging evidence that LPI lipids can also serve as relevant lipid signals promoting proinflammatory, profibrotic, and endothelial-activating effects (37,(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). Several recent articles have shown that the MBOAT7 substrate LPIs (16:0, 18:0 LPI, and 18:1 LPI) can initiate rapid signaling processes in macrophages and endothelial cells to promote inflammatory cytokine production as well as endothelial cell activation (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102).…”
Section: So the Key Question Still Remainsmentioning
confidence: 99%
“…Although a plethora of research has been conducted with lysophosphatidic acid and sphingosine-1-phosphate, there is emerging evidence that LPI lipids can also serve as relevant lipid signals promoting proinflammatory, profibrotic, and endothelial-activating effects (37,(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). Several recent articles have shown that the MBOAT7 substrate LPIs (16:0, 18:0 LPI, and 18:1 LPI) can initiate rapid signaling processes in macrophages and endothelial cells to promote inflammatory cytokine production as well as endothelial cell activation (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). Given that ASO-mediated knockdown of Mboat7 resulted in the accumulation of LPI lipids in the liver (37,38,40), Helsley et al followed up on this observation to demonstrate that only two intraperitoneal doses of exogenous 18:0 LPI or 18:1 LPI were able to stimulate proinflammatory and profibrotic gene expression in the liver in Mboat7 knockdown mice but not in control mice where MBOAT7 activity is sufficient to esterify the exogenous LPI (37).…”
Section: So the Key Question Still Remainsmentioning
confidence: 99%
“…Previous studies reported that lysophosphatidylcholine (LPC) and oxidized low-density lipoprotein (oxLDL) induce Nod-like receptor family 3 (NLRP3) and promote endothelial cell activation ( 26 28 ) in cardiac diseases ( 29 ). Further, the activation of caspase-1 canonical inflammasome pathway and caspase-4 (human)/ caspase-11 (mice) noncanonical inflammasome pathway will lead to gasdermin D cleavage and N-terminal gasdermin D protein pore formation on the plasma membrane, which could mediate endothelial pyroptosis during atherosclerosis development ( 30 32 ). In addition to pyroptosis, necroptosis, and mitochondrially mediated necrosis are the other common cell death pathways observed in heart diseases.…”
Section: Lytic Programmed Cell Death and Its Role In Inflammation Of ...mentioning
confidence: 99%